2014
DOI: 10.5194/bg-11-1981-2014
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary and atmospheric sources of iron around South Georgia, Southern Ocean: a modelling perspective

Abstract: Abstract. In high-nutrient low-chlorophyll waters of the western Atlantic sector of the Southern Ocean, an intense phytoplankton bloom is observed annually north of South Georgia. Multiple sources, including shallow sediments and atmospheric dust deposition, are thought to introduce iron to the region. However, the relative importance of each source is still unclear, owing in part to the scarcity of dissolved iron (dFe) measurements in the South Georgia region. In this study, we combine results from a recently… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 78 publications
(206 reference statements)
2
39
1
Order By: Relevance
“…1) (Borrione et al, 2014;Nielsdóttir et al, 2012). Based on our study, the main DFe sources during this passage of the ACC were benthic release and vertical mixing, release of DFe from krill and krill faecal pellets, and supply of particles from run-off and glacial melt-water.…”
Section: Iron Budget In the Bloom Regionmentioning
confidence: 79%
See 4 more Smart Citations
“…1) (Borrione et al, 2014;Nielsdóttir et al, 2012). Based on our study, the main DFe sources during this passage of the ACC were benthic release and vertical mixing, release of DFe from krill and krill faecal pellets, and supply of particles from run-off and glacial melt-water.…”
Section: Iron Budget In the Bloom Regionmentioning
confidence: 79%
“…This indicates that DFe was quickly removed from ACC surface waters following passage of the island. However, previous studies in the region suggest DFe transfer beyond the shelf break of South Georgia (Borrione et al, 2014;Nielsdóttir et al, 2012). Nielsdóttir et al (2012) (2012) were also obtained during the summer season but indicated rapid reduction in concentrations through mixing with DFe-depleted ACC water, biological uptake, and/or particle scavenging (authigenic precipitation).…”
Section: Offshore Transport Of Trace-metal-enriched Water Massesmentioning
confidence: 86%
See 3 more Smart Citations